EFL Students’ Perceptions of Difficulties in Listening Section For TOEFL - Paath, Gabrilia M.; Pelenkahu, Noldy; Tuerah, Ignatius J. C. (English Education Department, 2024)
The aim of the research is to reveal students’ perception of difficulties in listening section for TOEFL by students of English Education Department UNIMA. This research used descriptive quantitative research. The techniques of collecting the data were questionnaire. The sample was 21-eighth semester students English Education Department UNIMA. The research finding showed that there are three types of difficulties faced by students. They are related with the material, related with the listener, and related with the physical setting. Bored and fatigue with long spoken text is difficulty that is most faced for the material because it has the percentage 90.5%. Difficult in the listening test because of the unclear of pronunciation is most faced by the students for the listener factor with the percentage 81%. Difficult to answer because of the bad quality of recording and difficult to concentrate if there are noises around the room of the listening test are most faced for the physical setting with the percentage 90.5%. Considering the result of this study, the students should be more active in practicing and need to train their listening at home intensively. English lecturers were suggested can decide which teaching strategies can be used to help the students improving their listening skills and can help them to overcome their problem in learning listening